Using soil classification to improve interpretation of biological soil health indicators - K.A. Congreves; Q. Wu (Geoderma)
The concept of soil health recognizes soil as a living and dynamic natural system, a notion that aptly fits in the realm of biology. However, soil health tests and scoring tools are often dominated by indicators other than soil biology, such as soil fertility and chemistry. Biological indicators of soil health remain understudied and underrepresented in soil health assessments. To address this gap, here we evaluate soil attributes that reflect biological functions and vitality (including organic and total C, total N, mineralized C, extracellular enzyme activity, and phospholipid fatty acid (PLFA) analysis for microbial biomass and adaptation response ratio (ARR)). We assess if these biological indicators can be contextualized by soil classification and measure their responsiveness to agricultural management practices in Prairie region of Saskatchewan Canada. Despite the dynamic nature of biological indicators of soil health, we find that soil classification by great group constrains measurements and serves as a useful contextualizing factor to adjust scoring functions. Further, we find biological indicators of soil health (namely soil organic C, total N, and P and S enzyme activity) generally improve with more regenerative crop production practices such as cover cropping or organic management. Although other indicators such as CO2 mineralization, N and C cycling enzymes, PLFA and ARR showed fewer differences among crop production practices, all were greater under prairie grassland than cropland. In contextualizing soil health scores by soil classification and including biological indicators of soil health that embody soil pools, processes, and life, soil health assessments will not only better represent soil biology and appropriately contextualize soil health scores, but also move towards better targeting soil functioning and vitality.